Inhibition of planktonic growth and biofilm formation of Staphylococcus aureus by entrectinib through disrupting the cell membrane - Liu, Shanghong; Xiong, Yanpeng; Xiao, Haitao; Zheng, Jinxin; Wen, Zewen; Li, Duoyun; Deng, Qiwen; Yu, Zhijian (Frontiers in Microbiology, 2023)
Over the last few decades, Staphylococcus aureus infection remain a major medical challenge and health concern worldwide. Biofilm formation and antibiotic resistance caused by S. aureus make it difficult to be eradicated from bacterial infections in clinics. In this study, our data demonstrated the antibacterial and excellent anti-biofilm activity of entrectinib against S. aureus. Entrectinib also exhibited the good safety, suggesting no toxicity with antibacterial concentration of entrectinib toward the erythrocytes and mammalian 239 T cells. Moreover, entrectinib significantly reduced the bacterial burden of septic tissue in a murine model of MRSA infection. Global proteomic analysis of S. aureus treated with entrectinib showed significant changes in the expression levels of ribosomal structure-related (rpmC, rpmD, rplX, and rpsT) and oxidative stress-related proteins (Thioredoxin system), suggesting the possible inhibition of bacterial protein biosynthesis with entrectinib exposure. The increased production of reactive oxygen species (ROS) was demonstrated in the entrectinib-treated S. aureus, supported the impact of entrectinib on the expression changes of ROS-correlated proteins involved in oxidative stress. Furthermore, entrectinib-induced resistant S. aureus clone was selected by in vitro induction under entrectinib exposure and 3 amino acid mutations in the entrectinib-induced resistant S. aureus strain, 2 of which were located in the gene encoding Type II NADH: quinoneoxidoreductase and one were found in GTP pyrophosphokinase family protein. Finally, the bactericidal action of entrectinib on S. aureus were confirmed by disrupting the bacterial cell membrane. Conclusively, entrectinib exhibit the antibacterial and anti-biofilm activity by destroying cell membrane against S. aureus.